Terconazole Cream for Non-Candida albicans Fungal Vaginitis: Results of a Retrospective Analysis - Geetika Sood; Paul Nyirjesy; M. Velma Weitz; Ashwin Chatwani (Hindawi Limited, 2000)
Objective: Although it is FDA-approved for use in vulvovaginal candidiasis caused by non-Candida albicans species, terconazole cream has not been been studied in patients with these infections. We sought to assess the clinical and mycological efficacy of terconazole cream in women with non-C. albicans vaginitis.